Towards An Integrated Framework for Special Economic Zones (SEZs): A Dynamic Institutional Approach - Aradhna Aggarwal (Copenhagen Business School (CBS), Asia Research Centre (ARC), 2017)
This paper presents a comprehensive conceptual framework for the rationale, success factors and development outcomes of Special Economic Zones (SEZs), and analyses their performance in selected Asian countries within that framework. It draws on the tenets of the literature on 'dynamics of institutional changes' to introduce basic assumptions and generates a series of propositions as building blocks of the framework. It argues that SEZs are a safety valve that can address inefficiencies within a given institutional context. If used strategically, the SEZ policy can be an exceedingly versatile tool to achieve a variety of goals. The drivers of success and economic outcomes of SEZs depend on the strategic approach adopted by policy makers towards SEZs. There is no single recipe of their success or development outcomes. Finally, institutions evolve in the process of development. So must strategic approaches towards SEZs. New genres of SEZs need to emerge and the existing ones must upgrade to address new institutional challenges, and achieve new goals. It argues that is the SEZ policy and not SEZs per se that need to be the focal point of the SEZ debate.
hdl:10398/9537
Keywords: 330; Special economic zones; Dynamic institutional Framework; Asian countries; Development outcomes; Success factors; Sonderwirtschaftszone; Entwicklung; Wettbewerbsvorteil; Erfolgsfaktor; Neue Institutionenökonomik; China; Südkorea; Taiwan